2016
DOI: 10.1053/j.gastro.2016.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1β Mediates Intestinal Inflammation in Mice and Patients With Interleukin 10 Receptor Deficiency

Abstract: IL10 receptor (IL10R)-deficient mice develop spontaneous colitis and similarly, patients with loss-of-function mutations in IL10R develop severe infant-onset inflammatory bowel disease (IBD). Loss of IL10R signaling in mouse and human macrophages is associated with increased production of interleukin 1 beta (IL1B). We demonstrated that innate immune production of IL1B mediates colitis in IL10R-deficient mice. Transfer of Il1r1−/− CD4+ T cells into Rag1−/−/Il10rb−/− mice reduced the severity of their colitis (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 17 publications
3
127
0
Order By: Relevance
“…Finally, and perhaps most importantly, it has been demonstrated that NLRP3 inflammasome hyperactivity and increased IL-1β secretion may mediate colitis in CD patients due to IL-10R deficiency. Therefore, these patients can successfully be treated with the IL-1R blocker anakinra (31). This evidence of a negative relation between IL-10 and the NLRP3 inflammasome may have a direct relevance to the gut inflammation in patients with the CARD8 mutation reported here, as it may be that the presence of a subtle IL-10 deficiency enhances the effect of the mutation on NLRP3 function and thus determines whether the mutation will cause inflammation.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, and perhaps most importantly, it has been demonstrated that NLRP3 inflammasome hyperactivity and increased IL-1β secretion may mediate colitis in CD patients due to IL-10R deficiency. Therefore, these patients can successfully be treated with the IL-1R blocker anakinra (31). This evidence of a negative relation between IL-10 and the NLRP3 inflammasome may have a direct relevance to the gut inflammation in patients with the CARD8 mutation reported here, as it may be that the presence of a subtle IL-10 deficiency enhances the effect of the mutation on NLRP3 function and thus determines whether the mutation will cause inflammation.…”
Section: Discussionmentioning
confidence: 55%
“…After 48h, there were 3537 differentially expressed (DE) genes between TH17-SAA1 and TH17-TGFb cells (Figure 2A). Compared to TH cells cultured in IL-6 alone or the TH17-TGFb condition, TH17-SAA1 cells exhibited a profound induction of hallmark chronic inflammatory disease-associated genes, such as Il23r (Abdollahi et al, 2016;Duerr et al, 2006;Gaffen et al, 2014;Hue et al, 2006), Il1r1 (Shouval et al, 2016) , and S100a4 (Oslejskova et al, 2009) (Figure S2B and S2C). Gene set enrichment analysis using previously defined TH17 datasets revealed a striking correlation with the "pathogenic" TH17 signature, but an anticorrelation with the "non-pathogenic" TH17 signature, as early as 3h after SAA treatment (Lee et al, 2012) (Figure 2B).…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, the production of IL‐1β is closely correlated with that of IL‐10 in patients with IBD and colitis and in animal models of colitis. For example, IL‐1β is highly produced by the macrophage of IL‐10 receptor–deficient mice and patients with disrupted IL‐10 receptors (46), and the transcription and secretion of IL‐1β is increased in the IL‐10–deficient mouse model of IBD (47, 48). Therefore, it will be interesting to investigate whether our new mechanism works in the TNBS‐induced and IL‐10–deficient mouse models of colitis.…”
Section: Discussionmentioning
confidence: 99%